Implementation of Epidemiological Surveys Monitoring in the Class III Airport in Banda Aceh - Safrizal Safrizal (Newinera Publisher, 2020)
Airport epidemiological surveillance is the monitoring of the arrival and departure of aircraft and passengers with the potential to cause disease and the risk of epidemics and outbreaks. The purpose of this study was to determine the operational performance analysis and epidemiological reporting in the Class III Airport area of Banda Aceh. This study uses an evaluative descriptive approach and case studies with surveys and direct observations in the field. Data collection techniques are done using secondary data and documentation studies. The results of the study there are significant differences between domestic and foreign flights and unknown flights with a significance value of 0,000 or less than 0.05. there is no significant difference between the incoming crew and the departing crew with a significance value of 0.752 or greater than 0.05 where t arithmetic is still lower than the threshold value of 1.96. There is a significant difference between the number of passengers arriving and the number of passengers leaving. This is seen from the significance value of 0.001 or smaller than the threshold value of 0.05, where t value (3,419) is greater than the threshold value of 1.96. So that it can be proven that the number of passengers arriving and departing is different There is no significant health difference between passengers arriving and passengers leaving from the SIM airport with a sig value of 0.259 or greater than 0.05 where t value is below 1.96. The health conditions of passengers arriving and departing throughout 2019 are the same.